The Impact of The 2022 Russian Invasion of Ukraine On The Indonesian Capital Market - Indra Alie Wijaya; Ni Ketut Rasmini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of the Russian invasion of Ukraine on February 24, 2022, on the Indonesian capital market, particularly on the stocks listed in the LQ45 index, as well as on exchange rates and cryptocurrency trading volumes. The research employs a quantitative approach using an event study method, focusing on a 15-day observation window—comprising 7 days before, the day of, and 7 days after the invasion event. The variables analyzed include abnormal return (AR), trading volume activity (TVA), exchange rates, and cryptocurrency transaction volume. The research sample consists of issuers listed in the LQ45 index and the three largest cryptocurrencies by market capitalization—Bitcoin, Ethereum, and Tether (USDT)—selected through purposive sampling. The findings indicate that the Russian invasion of Ukraine had a significant impact on abnormal returns and trading volume activity of LQ45 stocks, as well as on exchange rates and cryptocurrency trading volumes. This geopolitical event emerged as an external factor contributing to market uncertainty, prompting investors to adjust their investment strategies in both stock markets and digital assets. These findings confirm that global conflicts are closely linked to the dynamics of domestic financial markets.